Quality of ambulatory care provided by physicians-in-training for common diseases before and after the Japanese government reformed post-graduate medical education - Shibuya, Katsuhiko; Miyashita, Atsushi; Noguchi, Yoshinori; Okamura, Shintaro; Soma, Masayoshi; Peabody, John W; Takeuchi, Yasuhiro; Arimura, Yasuji; Fukumoto, Yohei; Shimada, Toshihiko; Ishimaru, Hiroyasu; Fukuhara, Shunich; et al. (Tenri Medical Bulletin, 2012)
The objective of this study is to evaluate the change in the quality of care provided by physicians-in-training in Japan for common diseases after the 2004 post-graduate medical education (PGME) reforms. Physicians who were training at eight Japanese teaching hospitals participated in this study. The physicians completed clinical performance vignettes involving outpatients with four common conditions (diabetes mellitus, chronic obstructive pulmonary disease, vascular disease, and depression). Their responses were judged against a master list of explicit evidence-based quality criteria to give a percentage of correct answers. We compared the scores obtained in 2003 with those recorded in 2008 to evaluate whether they improved after rotating curricula had been put in place. In 2003, 141 (70.1%) students consented to participate, whereas in 2008, 237 (72.3%) consented to participate. We did not observe any significant change in the quality of care score after adjusting for possible confounders (change in the total score from 2003 = 1.9, 95% CI: -1.8 to 5.8). The quality of care score improved by 3.1 percentage points at the institutes whose pre-reform curricula were specialty-oriented, which was significantly greater than the 1.4 point increase observed at the institutions whose pre-reform curricula involved rotation (p-value for interaction, 0.03). The quality of care provided by physicians-in-training for diseases that are commonly encountered by general internists did not change after the 2004 PGME reforms.